2020
DOI: 10.1186/s43014-020-00040-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural bioactive substances for the control of food-borne viruses and contaminants in food

Abstract: Food-borne viruses and contaminants, as an important global food safety problem, are caused by chemical, microbiological, zoonotic, and other risk factors that represent a health hazard. Natural bioactive substances, originating from plants, animals, or microorganisms, might offer the possibility of preventing and controlling food-borne diseases. In this contribution, the common bioactive substances such as polyphenols, essential oils, proteins, and polysaccharides which are effective in the prevention and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 174 publications
0
8
0
Order By: Relevance
“…Furthermore, catechol groups are also present in a variety of phenolic compounds found in Origanum bastetanum extract, such as luteolin, luteolin rutinoside or amburoside A. It has been previously reported that the antiviral activity of these phenolic compounds found in oregano essential oils is related to the damage of the virus capsid for FCV [50]. These findings were also supported by other vegetable samples, such as green tea extract (GTE), on virus like-particles of human norovirus [51].…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, catechol groups are also present in a variety of phenolic compounds found in Origanum bastetanum extract, such as luteolin, luteolin rutinoside or amburoside A. It has been previously reported that the antiviral activity of these phenolic compounds found in oregano essential oils is related to the damage of the virus capsid for FCV [50]. These findings were also supported by other vegetable samples, such as green tea extract (GTE), on virus like-particles of human norovirus [51].…”
Section: Discussionmentioning
confidence: 75%
“…In this study, the mode of action of hydrosols against NoV was not investigated. Previous studies have revealed that the virucidal mechanism of plant compounds on nonenveloped viruses can vary, including 1. degradation of the viral capsid or nucleic acid; 2. interference with the absorption of the virus on the host cells by binding to the surface of the virus; and 3. interference with the attachment of the viral surface protein to the cellular receptors [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…EOs are widely reported as possessing antimicrobial, antimycotic, antiparasitic and insecticidal properties against human pathogens [ 6 , 7 , 8 , 9 , 10 , 11 ]. The antiviral efficacy of EOs has also been evaluated [ 12 ]. In recent years, EOs have more often been investigated against enveloped viruses [ 13 , 14 , 15 ], while to date, only limited research has looked at the efficacy of EOs against non-enveloped viruses [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%